The Menstrual Period in Qur’an: Interpretation of Al-Baqarah verse 222 - Ramdan, Aldi; Arrashif, Gitsa Yatna; Hawari, Ibnu Muhammad; Nursadin, Kahfi Maulana; Suhartawan, Budi (Institut Agama Islam Persis Bandung, 2023)
This article contains how Menstrual Periods are usually experienced by women caused by the lunar cycle. Science and the Qur'an have studied Menstruation starting from cycles, factors, phases and cleanliness. Menstruation has become a problem that is widely discussed by women, especially because it affects their religious obligations, this encourages the importance of studying this matter. This study uses a qualitative method with a library research approach. In this article, we find a scientific link to menstruation in the Qur'an